2015
DOI: 10.1016/j.mod.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Id2a is required for hepatic outgrowth during liver development in zebrafish

Abstract: During development, inhibitor of DNA binding (Id) proteins, a subclass of the helix-loop-helix family of proteins, regulate cellular proliferation, differentiation, and apoptosis in various organs. However, a functional role of Id2a in liver development has not yet been reported. Here, using zebrafish as a model organism, we provide in vivo evidence that Id2a regulates hepatoblast proliferation and cell death during liver development. Initially, in the liver, id2a is expressed in hepatoblasts and after their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Using a morpholino-mediated knockdown approach, we previously reported that during liver development Id2a positively regulates hepatic outgrowth through hepatoblast proliferation and survival. (31) However, we found that during BEC-driven liver regeneration Id2a negatively regulates the proliferation of newly generated BECs. Although we did not detect any developmental defects in the id2a -/mutants, inconsistent with the morpholino results, this discrepancy might be explained by the genetic compensations that can occur in mutants but not in morphants.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Using a morpholino-mediated knockdown approach, we previously reported that during liver development Id2a positively regulates hepatic outgrowth through hepatoblast proliferation and survival. (31) However, we found that during BEC-driven liver regeneration Id2a negatively regulates the proliferation of newly generated BECs. Although we did not detect any developmental defects in the id2a -/mutants, inconsistent with the morpholino results, this discrepancy might be explained by the genetic compensations that can occur in mutants but not in morphants.…”
Section: Discussionmentioning
confidence: 67%
“…Using a morpholino‐mediated knockdown approach, we previously reported that during liver development Id2a positively regulates hepatic outgrowth through hepatoblast proliferation and survival . However, we found that during BEC‐driven liver regeneration Id2a negatively regulates the proliferation of newly generated BECs.…”
Section: Discussionmentioning
confidence: 77%
“…Hence, we analyzed the function of Id2, which has been shown to suppress the function of Neurod [ 19 ] and an immediate target of Bmp signaling [ 18 ]. Zebrafish have two id2 genes: id2a and id2b [ 53 ]. Only id2a is expressed in the liver from 30 hpf onwards [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zebrafish have two id2 genes: id2a and id2b [ 53 ]. Only id2a is expressed in the liver from 30 hpf onwards [ 53 ]. We conducted loss-of-function analyses using published id2a MO [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, Id2a maintains hepatoblast number(Khaliq et al, 2015). Ida2 controls hepatoblast proliferation and also promotes cell survival independent of proliferation through two downstream targets: Anxa4 and Nexin7 (Zhang et al, 2014).…”
Section: Liver Development: Zebrafish As a Paradigmmentioning
confidence: 99%